Analisa Kemiringan Sudut Tiga Bilah dan Empat Bilah Pada Turbin Angin Hawt - Hutabarat, Michael A G; J, Junaidi; Y, Yulfitra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Population growth is one of the factors causing the increasing demand for energy. This increase in energy demand is accompanied by a decrease in the number of existing energy sources such as coal, natural gas and oil. Therefore a solution is needed to overcome this limitation, namely by looking for alternative energy sources that are renewable and environmentally friendly, so that they can be used widely and continuously. One source of renewable and environmentally friendly energy is wind power. The purpose of this study was to analyze the slope angle of the 3-blade and 4-blade horizontal axis wind turbines. In addition, this study also aims to determine the output power, power coefficient, and tip speed ratio of the wind turbine. This study used aluminum plate material with a blade length of 120 cm and a width of 12 cm with a generator power of 500 rpm. The results showed that the output power obtained was 8.65 A, the wind turbine power coefficient was 59% and the tip speed ratio was 7.45 rad/s. In these conditions shows that the wind speed and blade diameter greatly affect the output power of the design results.